Facteurs de risque de la tuberculose multi-résistante dans la ville de Kinshasa en République Démocratique du Congo - Misombo-Kalabela, André (Pan Afr Med J, 2016)
BACKGROUND: The aim of this study was to determine the risk factors for multidrug-resistant tuberculosis (TB) in the city of Kinshasa in the Democratic Republic of Congo. METHODS: This was a case control study. The cases included all TB patients notified as resistant to rifampicin and isoniazid in Kinshasa from January 2012 to June 2013. The controls included TB patients treated during the same period as the cases and declared cured at the end of treatment. For this study, we obtained ethical clearance. RESULTS: The sample consisted of 213 participants, 132 men (62%) and 81 women (38%). The median age was 31 years (16-73 years). Factors associated with significant (p< 0,05) multidrug-resistant tuberculosis were the non-observance of the hours of taking drugs (0R = 111) (80% cases, 4% controls), the failure of treatment (0R = 20 (76% cases, 13% controls); the concept of multidrug-resistant tuberculosis in the family (0R = 6.4) (28% cases, 6% controls); a lack of knowledge of multidrug-resistant tuberculosis (0R = 3.2) (31% cases, 59% controls); a stay in prison (0R = 7.6) (10% cases, 1% controls) and the interruption of treatment (0R = 6.1) (59% cases, 19% controls). CONCLUSION: The emergence of multidrug-resistant tuberculosis can be avoided by the installation of suitable diagnosis and treatment strategies.